Role of Nurse as Care Giver and Advocator In The Ward, Era National Health Insurance (NHI) Program - Indriati, Indriati; Hartoyo, Mugi; Dwiningsih, Sri Utami (Journal Of Nursing Practice, 2018)
Background: There are many National Health Insurance (NHI) participants who do not yet understand the mechanism of NHI services, including clients who are hospitalized. The phenomena that exist on the field, that the client will enlist the help of health professionals who are always in the ward, especially nurses, to provide information on all matters, including NHI. On the other hand, nurses have a major role in caring for clients, based on their duties and functions. Purpose : This study aims to determine if there is expansion of the role of nurses as care giver and advokator in the inpatient unit, era NHI program. Methods : This research is a descriptive study of the role of nurses as care giver and advokator in inpatient era NHI program, employing triangulation method. Respondents were 64 inpatient clients registered as NHI participants in the Hospital Semarang assigned by proportional simple random sampling, and four nurses. Result : The results showed that there are expanding the role of nurses as care giver and advocator in the inpatient unit, era NHI program. Conclusion : With the implementation of NHI program, the roles of nurses as care giver and advokator has expanded in the inpatient unit. BPJS/NHI parties need to disseminate information relating to NHI to nurses, as well as the need to be given compensatory reward for nurses